Biosorption of Nickel Ions by Immobilized Brown Algae Laminaria japonica - Fan, Wenhong; Xu, Zhizhen; Feng, Lijuan; Li, Qian (Asian Journal of Chemistry, 2011)
Brown alga Laminaria japonica was immobilized using sodium alginate and glutin and used as biosorbent for removal of Ni2+ from aqueous solutions. The preparation conditions of the adsorbent beads were optimized by determining the optimal concentrations of the sodium alginate and glutin solution and the dose of L. japonica. The biosorption equilibrium of Ni2+ by the immobilized L. japonica beads is reached at 180 min. The initial pH of 4-7 has no appreciable influence on nickel biosorption. When the biosorbent dose is increased, nickel biosorption capacity decreases, whereas removal efficiency increases. An EDTA solution of 0.001 mol/L is the better desorbent. The regenerated biosorbent can be reused, with biosorption capacity decreasing by only 18 % after 5 cycles.